STABLE CHLORINE ISOTOPES IN HALITE AND BRINE FROM THE GULF COAST BASIN: BRINE GENESIS AND EVOLUTION - Eastoe C.J.; Long A.; Land L.S.; Kyle J.R. (My University, 2001)
Stable chlorine isotope data, used in conjunction with other geochemical parameters, are useful in determining the origin of solute in formation waters with salinity different from that of seawater. Jurassic salt in the Gulf Coast Basin has δ37Cl ranges of -0.5%% to 0.3%% (bedded) and 0.0%% to 0.5%% (diapiric). The values for bedded salt are consistent with a δ37Cl value of 0.0%% for Jurassic seawater chloride, as in modern oceans. The slightly higher values for diapiric salt are possibly caused by incongruent solution of halite. Formation waters have a δ37Cl range of -1.9%% to 0.7%%. Waters with δ37Cl<-0.6%% have been found in siliciclastic strata of Eocene to Miocene age, but not in Plio-Pleistocene strata or in Mesozoic carbonate rocks. Brine with δ37Cl near 0.0%%, as expected for incongruent dissolution of halite, has mixed with low-salinity water in Eocene to Miocene strata. Unevolved seawater is present in Plio-Pleistocene strata. Mesozoic strata contain brine with δ37Cl>-0.2%%. Low-salinity water from geopressured aquifers appears to have resulted from shale dewatering. Low δ37Cl values in such water are related to low mCl/mNa (a parameter indicating dewatering) but show no general relationship to Cl/Br. They are consistent with diffusion of chloride from allochthonous brine. Diffusion can generate domains of water with negative δ37Cl on a scale of hundreds of meters in 104-106 years, and may also generate positive-δ37Cl chloride in residual source brine.
Keywords: CL-37/CL-35; GULF OF MEXICO; SALT; BRINES; DIFFUSION